(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study analyzes Prabowo Subianto’s strategic rebranding from an authoritarian military figure to a ’Gemoy’ (charmingly humorous) persona during Indonesia’s 2024 presidential election, which targeted the youth vote comprising over 56% of the electorate. Employing a qualitative approach, including interviews with campaign insiders and digital analytics framed by Norton’s communication style theory, the research identifies animated, expressive, and relaxed-impression-leaving styles as central to this transformation. Findings reveal that this digitally-driven affective strategy, particularly through viral TikTok content, successfully reshaped his public image and resonated strongly with millennial and Gen-Z voters, directly contributing to his electoral victory. The study concludes that emotional relatability and digital populism are now decisive factors in modern political branding.